Rethinking professional standards to promote professional learning. Issue 1 (1st January 2016) - Forde, Christine; McMahon, Margery Anne; Hamilton, Gillian; Murray, Rosa
Abstract : This article explores some of the key issues that emerged in the revision of the professional standards in Scottish education. The revision of the professional standards was part of a wider project to build teacher professional learning in ways that had an impact on practice and on pupil learning. The article begins by examining the international literature to consider the two critical aspects of the design and the use of professional standards. The article then explores issues raised in the work to take forward the two recommendations from the Donaldson report related to, firstly, the professional standards providing a coherent framework and, secondly, the development of a 'standard for active registration'. The article then considers the tensions posed by the dual purposes ascribed to standards, those of regulation and development. The focus then turns to an alternative way of constructing a professional standard in order to foster authentic forms of professional learning. The article concludes by exploring the issues that need to be addressed to facilitate the productive use of professional standards in the career-long professional learning of teachers.